Effects of consumer motivational factors on acceptance of sports event tourism websites and intention to use the websites - Radzuwan, Radzliyana; Khor, Poy Hua; Abdul Aziz, Azlan; Lim, Khong Chiu (2014)
Previous studies on the uses and gratification theory (U & G) suggested that consumer motivational factors affect how they will consume the media and media contents.Recent marketing research has extended the theory to study the use of websites as a marketing and communication tools.The current study investigates the moderating effects of acceptance of sports event websites (ASETW) and intention to use the websites.Initially, components of acceptance of sports event tourism websites were developed based on the Sport Website Acceptance Model (SWAM). These components consisted of accessibility, flexibility, interactivity and reliability.As online consumers have been assumed to be actively involved in their Internet and website marketing, it is important for present researchers understand why online consumers choose to utilize the Internet and websites as well as to investigate the moderating effects of motivational factors on the relationship between acceptance and intention to use the websites.A sample of the study comprised of 530 local and international tourists participated in three selected sports event tourism conducted in Malaysia in 2013 (315 males and 215 females).A simple random sampling technique was applied to select these respondents. Results of regression analysis show that there was a significant relationship between acceptance and intention to use the websites.In order to determine the effects of motivational factors as the moderating variables that moderate the relationship between independent and dependent variable, a multiple regression analysis through the stepwise method was carried out.Results show that this study indicates only 14.8% of the total variation of intention to use the websites was explained by accepting, entertainment gratification, informativeness gratification, moderator entertainment gratification and moderator informativeness gratification.The findings of this study suggest that future researchers in academia and tourism industry may include other moderating attributes apart from the ones mentioned here when developing and providing online information marketing and communication through tourism websites.